ANALISIS STRATEGI KOMUNIKASI KONTEN EDUKATIF PADA AKUN TIKTOK @SILVIA_ASSOBURU - Musdalipah; Silvia Assoburu; Irpinsyah (STKIP Subang, 2026)
This study aims to analyze the communication strategies used in delivering educational content on the TikTok account @silvia_assoburu. The focus of this research is to examine how content strategies are implemented in conveying educational messages and how audiences respond to such content. This study employs a qualitative approach using content analysis techniques on several types of content, including thesis supervision, campus introduction, student thesis defense, and classroom activities.The results show that the communication strategies applied include the use of engaging hooks at the beginning of videos, authentic (real-life) visual presentations, the use of natural audio and relevant background music, as well as concise, clear, and easily understandable message delivery. Content that incorporates emotional elements and real academic experiences is proven to be more effective in attracting attention and increasing audience engagement. Furthermore, audience responses, as reflected in the comment section, indicate positive reactions such as empathy, appreciation, pride, motivation, and educational aspirations. Therefore, the TikTok account @silvia_assoburu is considered effective as a communication medium for delivering educational content, as well as in building a positive institutional image and emotional connection with the audience. This study is expected to serve as a reference for developing digital communication strategies, particularly in utilizing TikTok as an educational media platform.